UNiRIDE shuttle service/ ride-hailing / Nurul Syuhada R. Azmi, Intan Zahida Ahmad Mustaza and Nurul Asyikin Ab Wahab - R. Azmi, Nurul Syuhada; Ahmad Mustaza, Intan Zahida; Ab Wahab, Nurul Asyikin (2018)
This case study provides a study on analysis and evaluation of the current situation that occurred in Universiti Teknologi MARA, Puncak Alam, Selangor (UiTM Puncak Alam). The study on the efficiency of the UNiRIDE shuttle service among the students of UiTM Puncak Alam in which students in university need transportation for them to go to the classes everyday besides using the public transportation such as bus. Methods of analysis include interview with the section manager of UNiRIDE and analyses the problem occurred and faced by the students. The findings of this case study shows that UNiRIDE offers high standard services and cheap fares, which befits students budget comparing to any other ride hailing services. Besides, UNiRIDE operated in university campuses where demand is strong and this study is examined due to students that are often dissatisfied with free buses provided by university because of long waiting time. This study also finds out that the amount of car provided by UNiRIDE for shuttle service is insufficient as the demand by students in university is high and there are many requests by users to use this service. Recommendations discussed include the company need to increase the number of car provided for this services and improve their service so that the students will feel more comfortable to use the service from UNiRIDE.